Psychodrama in the time of Coronavirus - Daniele Regianini; Diana Botti (Forum for Group Psychotherapies and Processes)
Our country, Italy, was the first country outside Asia to be hit by the SARS-CoV-2 pandemic. As the virus increased in intensity and spread with increasing rapidity, the Italian government was forced to adopting a massive series of health measures, which strongly conditioned social interactions. For three months, normal group psychodrama sessions (other things) were banned. In order to keep existing groups alive and, therefore, make the most of the beneficial effects of interaction between members, modern digital communication technologies were widely used. These means of communication allowed us to maintain relationships, albeit without direct contact or a physical presence. By looking at a series of activities planned for one session (the fourth online session), this article endeavours to highlight how this particular kind of interaction can also promote interpersonal and intrapsychic dynamics according to the Morenian model.